Interest of Slovene Students in Listening to Various Musical Genres - Barbara Sicherl Kafol; Olga Denac; Jerneja Žnidaršič (Muzikološki Zbornik, 2016)
The aim of the study was to find out which musical genres are young people’s favourite, why they listen to those specific genres and which genres they used to listen to in their childhood together with their parents. The results show that most students‘s favourite genres are pop, rock, RnB and popular folk music. The results confirm that the choice of genres listened to together with parents during childhood affects musical preferences of students.